Self-esteem among high achievers of Islamic Revealed Knowledge and Human Sciences students - Mamat, Siti Salwani; Ismail, Siti Sarah Falwani; Md Nor, Siti Zanariah; Mohamed Saris, Siti Zuraidah; Idrus, Tia Ifzan; Mohd Mahudin, Nor Diana (2007)
A survey was conducted to investigate the relationship between self-esteem and high academic achievement. It is hypothesized that high academic achievers are more likely to possess high self-esteem. Fifty undergraduate students (41 females and 9 males) who received Dean’s List and obtained a GPA of 3.50 and above were contacted and selected as respondents. The questionnaire used to evaluate self-esteem was a modified version combining Rosenberg’s Self Esteem Scale and Coopersmith’s Self Esteem Inventory with some additional items developed by the present researchers. The correlational analysis showed a significant, positive correlation between self-esteem and high academic achievement with r = .626, p < .001. The implications, limitations, and suggestions of the study are discussed.